2019
DOI: 10.1310/sci18-00026
|View full text |Cite
|
Sign up to set email alerts
|

Early Colostomy Formation Can Improve Independence Following Spinal Cord Injury and Increase Acceptability of Bowel Management

Abstract: Background: Colostomy formation can solve complications of bowel management following spinal cord injury (SCI). Newly injured patients at this spinal unit have chosen colostomy as a preferred option for bowel management. Objectives: To discover the reasons patients choose colostomy formation early following SCI and make comparison with those choosing it later, and to establish whether early colostomy is safe and advisable. Methods: Medical and nursing records of patients with SCI who chose to have a colostomy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 22 publications
0
12
0
Order By: Relevance
“…Bowel dysfunction develops fairly rapidly after SCI 31,34 , and colostomy formation within 12 months of SCI could be a safe and effective way of gaining independence and making bowel care easier 35 .…”
Section: Discussionmentioning
confidence: 99%
“…Bowel dysfunction develops fairly rapidly after SCI 31,34 , and colostomy formation within 12 months of SCI could be a safe and effective way of gaining independence and making bowel care easier 35 .…”
Section: Discussionmentioning
confidence: 99%
“…Other studies reported higher percentages of rectal discharge in individuals with SCI. Boucher et al retrospectively studied 72 participants with SCI with either early colostomy formation (in the first few months after onset SCI; 20 participants) or late colostomy formation (after at least one year; 52 participants) [ 16 ]. Early complication rates did not differ between both groups.…”
Section: Discussionmentioning
confidence: 99%
“…The optimal timing of instituting the colostomy is open for discussion. In a retrospective study, Boucher et al 224 evaluated patients who were identified as having a colostomy "early, " in the first few months after SCI, and those who chose "later, " usually more than a year after injury and being discharged home. Early complication rates in both groups were low.…”
Section: Colostomy Can Be a Choice For Individualsmentioning
confidence: 99%
“…Overall, 20.8% of the individuals in this study who had previously been reliant on caregivers gained independence. 224 Co-management with an enterostomal therapist prior to surgery and in follow-up optimizes outcome. Colostomy has been compared with conservative management bowel programs and found to have equivalent or superior QOL outcomes.…”
Section: Colostomy Can Be a Choice For Individualsmentioning
confidence: 99%